The Psychological Effects of Social Media Use: Insights from Combined Research on Adolescents’ Mental Health - Bednarek, Szymon; Górski, Mateusz; Załęska, Adrianna; Bychowski, Mateusz; Kwaśna, Julia; Kaźmierczyk, Izabela; Lenart, Kacper; Homza, Michał; Zakrzewska, Natalia; Kulicka, Joanna (Quality in Sport, 2024)
This study delves into the intricate connection between social media usage and mental health outcomes in adolescents. It aims to amalgamate results from various research studies to unveil trends and establish causal relationships concerning social media engagement, sleep quality, self-esteem, anxiety, and depression. A meta-analytic approach was utilized, consolidating information from 21 articles across diverse fields of psychology, public health, and adolescent behavior research. These studies investigated quantitative and qualitative facets of social media influence, emphasizing factors like general usage trends, nighttime-specific usage, and emotional engagement with social platforms. Standardized assessments of mental well-being, such as the Pittsburgh Sleep Quality Index (PSQI), the Hospital Anxiety and Depression Scale (HADS), and the Rosenberg Self-Esteem Scale (RSES), were scrutinized to maintain uniformity in the analysis. The primary outcomes suggest that extensive engagement with social media, especially at night, is closely tied to diminished sleep quality, heightened anxiety and depression, and reduced self-esteem. Emotional engagement on social platforms plays a crucial role in predicting adverse mental health effects, influenced by levels of anxiety and depression. Notably, using social media at night is consistently associated with disturbed sleep cycles, intensifying psychological anguish. This research emphasizes the crucial necessity for implementing specific interventions to regulate teenagers' social media engagement, especially at night. The results emphasize the significance of emotional involvement and habitual usage trends as pivotal subjects for future investigation and actionable measures to improve the well-being of adolescents. These observations are vital for guiding policy decisions, educational campaigns, and clinical approaches aimed at enhancing mental health outcomes in the era of digital technologies.